Tangent Hyperbolic Fluid Flow under Condition of Divergent Channel in the Presence of Porous Medium with Suction/Blowing and Heat Source: Emergence of the Boundary Layer - Sushila Choudhary; Prasun Choudhary; Balachandra Pattanaik (International Journal of Mathematics and Mathematical Sciences)
A boundary layer’s appearance in a diverging permeable channel for a non-Newtonian hyperbolic tangent fluid with heat transfer in the availability of a heat source and suction or injection is investigated. By controlling backflow, nonlinearly associated ODEs are derived from flow-regulating PDEs, and the restrictions under which the formation of a boundary layer for tangent hyperbolic fluid emerges are investigated. It is obtained that mass suction is an expression of the Hartmann number, porosity parameter, and power law index parameter, and when it surpasses a specific quantity, flow within a boundary layer is conceivable. “Bvp4c,” a MATLAB solver, is used to obtain numerical solutions of flow problem, and for validation of results obtained via Bvp4c, a comparison is made with the methodology of the Runge–Kutta fourth order. As the Weissenberg number enhances, flow in a boundary layer decreases. Furthermore, radiation and heat source parameters have a significant influence on the overall temperature pattern, and as the findings, the thermal boundary layer enhances.